The Effect of Current Ratio, Total Asset Turnover, Debt to Equity Ratio on Return on Equity in Property Sub-Sector Companies Listed on the Indonesia Stock Exchange for the 2018-2021 Period - Tasya Dhea Meilita; Wahyudiono (NAROTAMA UNIVERSITY, Indonesia, 2023)
This study aims to determine the effect of Current Ratio, Total Asset Turnover, and Debt to Equity Ratio on Return On Equity in Property Sub Sector Companies on the Indonesia Stock Exchange for the 2018-2021 Period. This study uses an associative approach. The population used in this study is the Property Sub Sector Companies on the Indonesia Stock Exchange for the 2018-2021 period with a total of 39 companies. The sample used in this study used 8 companies that met the criteria with the purposive sampling method. The data analysis technique used in this study uses multiple linear regression, classical assumption test, hypothesis test, and coefficient of determination test. Data processing in this study used the IBM SPSS 26 program. The results showed that partially Current Ratio has a significant effect on Return On Equity, Total Asset Turnover has a significant effect on Return On Equity and Debt to Equity Ratio has no significant effect on Return On Equity. Meanwhile, simultaneously Current Ratio, Total Asset Turnover, and Debt to Equity Ratio have a significant effect on Return On Equity.